2014
DOI: 10.1088/1741-2560/11/5/056007
|View full text |Cite
|
Sign up to set email alerts
|

Detecting awareness in patients with disorders of consciousness using a hybrid brain–computer interface

Abstract: Through the hybrid BCI system, command following was detected in four healthy subjects, two of 7 DOC patients, and one LIS patient. We suggest that the hybrid BCI system could be used as a supportive bedside tool to detect awareness in patients with DOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 58 publications
0
76
0
1
Order By: Relevance
“…And the experimental result indicated that our approach had the higher classification accuracy and ITR. Recently, several SSVEP-based hybrid BCIs had been developed for increasing classification accuracies Wang et al, 2014;Pan et al, 2014). Our algorithm could be considered as a reliable method for improving the efficiency of these hybrid BCIs.…”
Section: Parametersmentioning
confidence: 99%
“…And the experimental result indicated that our approach had the higher classification accuracy and ITR. Recently, several SSVEP-based hybrid BCIs had been developed for increasing classification accuracies Wang et al, 2014;Pan et al, 2014). Our algorithm could be considered as a reliable method for improving the efficiency of these hybrid BCIs.…”
Section: Parametersmentioning
confidence: 99%
“…Multi-disciplinary studies including functional neuroimaging and electrophysiological recording, namely PET, fMRI and BCI, have also been performed in our laboratory (66,67). In addition, our group has established cooperation among research institutes and non-governmental organizations to promote the welfare of DOC patients, with an ultimate goal of establishing the first DOC society in China.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies mainly focused on using BCI to detect the awareness of DOC patients [13][14][15]. These studies determined whether patients were aware by verifying whether the patients followed commands.…”
Section: Discussionmentioning
confidence: 99%
“…Several BCI systems have recently been applied in awareness detection for patients with DOC [13][14][15][16]. Cruse et al accessed 16 VS patients by having them complete a motor imagery (MI) task in which they were instructed to imagine movements of their right hand and toes in response to commands [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation